2012
DOI: 10.1007/s12185-012-1117-7
|View full text |Cite
|
Sign up to set email alerts
|

AKT3, ANGPTL4, eNOS3, and VEGFA associations with high altitude sickness in Han and Tibetan Chinese at the Qinghai-Tibetan Plateau

Abstract: Mountain sickness (MS) occurs among humans visiting or inhabiting high altitude environments. We conducted genetic analyses of the AKT3, ANGPTL4, eNOS3 and VEGFA genes in lowland (Han) and highland (Tibetan) Chinese. Ten single nucleotide polymorphisms (SNPs) were evaluated in Han and Tibetan patients with acute (A) and chronic (C) MS. We compared 74 patients with AMS to 79 Han unaffected with MS, as well as 48 CMS patients to 31 unaffected Tibetans. The ten SNPs studied are AKT3 (rs4590656, rs2291409), ANGPTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 54 publications
4
63
0
Order By: Relevance
“…The people from the control group had lived at the 3600 M altitude for at least six months prior to being sampled. These sampling procedures have been previously described [8][9][10]31].…”
Section: Samplingmentioning
confidence: 99%
See 4 more Smart Citations
“…The people from the control group had lived at the 3600 M altitude for at least six months prior to being sampled. These sampling procedures have been previously described [8][9][10]31].…”
Section: Samplingmentioning
confidence: 99%
“…The Vector NTI Advance 11 computer program from Invitrogen, Carlsbad, CA, was used to develop the primers for genotyping each SNP. The genotyping methods and genotyping for each SNP have been previously outlined and reported [8][9][10]31]. The SNPs and genes used in the present study are found in (Table 1).…”
Section: Genotypingmentioning
confidence: 99%
See 3 more Smart Citations